Does State or Local Government Support for Small Businesses Attract Better Entrepreneurs? - KAYA, Halil Dincer (Journal of Advanced Research in Management; Vol 9 No 1 (2018): JARM Volume IX Issue 1(17) Summer 2018DO - 10.14505//jarm.v9.1(17).01, 2018)
In this study, we examine the relation between government support for small businesses and owner characteristics. Does government support attract certain types of entrepreneurs into an area? We find that more experienced and politically more conservative entrepreneurs tend to concentrate in the high-state government support score states. Also, there are fewer community college graduates and more technical college graduates among the owners in these states. When we examine the impact of local government support, we find that less experienced owners tend to concentrate more in the high-local government support score states while more experienced owners tend to concentrate more in the low-local government support score states. We also find that more experienced entrepreneurs and more conservative people tend to concentrate in the high-local government support score states. Our results show that there are more owners with technical college diplomas and fewer owners with an undergraduate degree among the owners in the high-score states. These findings indicate that entrepreneurs with certain characteristics are more concentrated in the high-government ( i.e . state or local) support score states. Therefore, if a state or a city/town wants to attract certain types of entrepreneurs into their area, they can use the findings here when making their policy decisions.